Lecturer Leadership In Digital Learning - Nasruji Nasruji; Indah Wahyuni; Abdul Chalim; Arief Yanto Rukmana; Fadloli Fadloli (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
The digital age requires lecturers to be able to package learning activities using digital technology. The aim of this study is to find out how lecturers lead their students in learning activities in the digital age and the impact of the digital era on learning and lecturers. This research is qualitative and descriptive, with observational data collection techniques and interviews. The result of this research is the expansion of the digital age, making students and faculty learn unlimitedly in space and time. Teachers need to prepare a learning plan related to the material and digital media that will be used. The use of digital media such as Google Forms, Google Class, and PowerPoint, various learning applications, bloggers, quizzes, Google Meet video conferences, and Zoom meetings has been used by lecturers. The negative impact is that (1) the learning material has become wider so that the essential material is not obtained; (2) the learning is less focused; (3) the lecturer is not always able to control each student's use of the gadget; and (4) the enthusiasm and ability of the senior lecturer still need to be improved. In conclusion, lecturers, as student leaders in learning, are expected to be able to effectively package the developments of the digital age to facilitate the implementation of learning.to effectively package the developments of the digital age to facilitate the implementation of learning.